POSHAN's abstract digest on maternal and child nutrition research - Issue 24 - Avula, Rasmi (International Food Policy Research Institute, 2018)
In this issue of Abstract Digest, we present to you a collection of articles on various aspects of nutrition, including its determinants, tools of measurement, and strategic responses through policy and program. Here are some of the highlights.